Genetic parameters for growth performance of the Malaysian local goats and their crossbreds with the German (improved) Fawn goats - Hirooka, H.; Mukherjee, T. K.; Panandam, J. M.; Horst, P. (Wiley, 1997)
Growth performance data of the local goats of Malaysia and their crossbreds with the German (Improved) Fawn goats were analysed using animal models with maternal effects, in order to estimate additive genetic and crossbreeding parameters. Two different genetic models, the Dickerson (1969, 1973) model and the Kinghorn (1980, 1983) model, were used to estimate crossbreeding parameters. Coefficients of additive breed, heterosis (dominance), and recombination (epistatic) loss were fitted in the animal models as covariates. In general, the individual breed effects for birth, 6-month, and 9-month weights, and maternal breed effects for traits until weaning, were significant, indicating large differences for growth performance between the German Fawn and the local breeds. Heterosis effects by the Dickerson model were small and non-significant, while dominance effects by the Kinghorn model, for some of traits, were large and significant. Highly significant individual recombination loss effects by the Dickerson model, and epistatic loss effects by the Kinghorn model, were obtained for birth and 9-month weights. The estimates of total heritability by an animal model incorporating maternal effects were moderate (0.18–0.35). The differences between heritabilities, estimated by different genetic models (the Dickerson model vs. the Kinghorn model), were small.